1999
DOI: 10.1016/s0029-7844(98)00459-1
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transmission of human papillomavirus from gravidas with latent infections

Abstract: Pregnant women with latent HPV infections have low potential of transmitting the virus to the oropharyngeal mucosae of their infants. The time between rupture of the amnion and delivery seems to be a critical factor in predicting transmission. Human papillomavirus-positive infants should be considered contaminated rather than infected since virus is cleared over several months after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
4
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 17 publications
3
53
4
2
Order By: Relevance
“…Twenty studies reported HPV rates Pakarian et al, 1994;Cason et al, 1995;Mazzatenta et al, 1996;Puranen et al, 1997;Chatterjee et al, 1998;Tseng et al, 1998;Watts et al, 1998;Xu et al, 1998;Tenti et al, 1999;Bandyopadhyay et al, 2003;Gajewska et al, 2005Gajewska et al, , 2006Rombaldi et al, 2008Rombaldi et al, , 2009Sarkola et al, 2008;Castellsague et al, 2009) in the mother and child and eight of them provided data on HR-HPV Cason et al, 1995;Tseng et al, 1998;Gajewska et al, 2006). Six studies were carried out in resource-restricted countries Tseng et al, 1998;Xu et al, 1998;Bandyopadhyay et al, 2003;Rombaldi et al, 2008Rombaldi et al, , 2009) and 14 in developed countries Pakarian et al, 1994;Cason et al, 1995;Mazzatenta et al, 1996;Puranen et al, 1997;Watts et al, 1998;Tenti et al, 1999;Gajewska et al, 2005Gajewska et al, , 2006Sarkola et al, 2008;Castellsague et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies reported HPV rates Pakarian et al, 1994;Cason et al, 1995;Mazzatenta et al, 1996;Puranen et al, 1997;Chatterjee et al, 1998;Tseng et al, 1998;Watts et al, 1998;Xu et al, 1998;Tenti et al, 1999;Bandyopadhyay et al, 2003;Gajewska et al, 2005Gajewska et al, , 2006Rombaldi et al, 2008Rombaldi et al, , 2009Sarkola et al, 2008;Castellsague et al, 2009) in the mother and child and eight of them provided data on HR-HPV Cason et al, 1995;Tseng et al, 1998;Gajewska et al, 2006). Six studies were carried out in resource-restricted countries Tseng et al, 1998;Xu et al, 1998;Bandyopadhyay et al, 2003;Rombaldi et al, 2008Rombaldi et al, , 2009) and 14 in developed countries Pakarian et al, 1994;Cason et al, 1995;Mazzatenta et al, 1996;Puranen et al, 1997;Watts et al, 1998;Tenti et al, 1999;Gajewska et al, 2005Gajewska et al, , 2006Sarkola et al, 2008;Castellsague et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were carried out in resource-restricted countries Tseng et al, 1998;Xu et al, 1998;Bandyopadhyay et al, 2003;Rombaldi et al, 2008Rombaldi et al, , 2009) and 14 in developed countries Pakarian et al, 1994;Cason et al, 1995;Mazzatenta et al, 1996;Puranen et al, 1997;Watts et al, 1998;Tenti et al, 1999;Gajewska et al, 2005Gajewska et al, , 2006Sarkola et al, 2008;Castellsague et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These may include mother-to-child vertical transmission [39][40][41][42], nonsexual transmission in children prior to their sexual debut [43], or auto-inoculation. For example, respiratory papillomatosis occurs as a consequence of both peripartum and sexual transmission [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies where high HPV prevalence rates amongst infant and/or child cohorts have been reported employed sensitive PCR techniques to detect small quantities of viral DNA (Mant et al, 2003;. In contrast, studies using MY09/MY11 consensus primers (Manos et al, 1989) for the detection of HPV DNA, often report low positivity rates (Puranen et al, 1996;Koch et al, 1997;Tenti et al, 1999), as this PCR has a far lower analytical sensitivity than type-specific PCRs (Gravitt et al, 2000;Perrons et al, 2002;Mant et al, 2003;Karlsen et al, 1996). The rate of positivity may also be influenced by the selection of sample transport media, the method of nucleic acid extraction and by the polymerase used (Castle et al, 2002).…”
Section: Hr Hpv Infections In Childrenmentioning
confidence: 99%